Option of Solid Pollutants Abatement in Flue Gas Path - Katarina Sulovcova; Jozef Jandacka (Communications - Scientific letters of the University of Zilina, 2013)
Biomass combustion produces gaseous and solid pollution. Solid pollutants are small particles which are getting into the air with smoke and may be harmful to the environment, the human and animal health. Therefore, it is important to decrease their amount in the ambient atmosphere. Particulate matter sources are not only big combustion devices but also small combustion devices which are quite common and widely used. It is necessary to mention that the small boilers are not as monitored as bigger ones. Therefore, they are potentially a large source of pollution. The main objective of this work is to reduce particulate matter concentration produced by small residential combustion appliances by making a change of the geometric parameters in a flue gas path.